2020
DOI: 10.1111/gcb.14968
|View full text |Cite
|
Sign up to set email alerts
|

Global‐scale species distributions predict temperature‐related changes in species composition of rocky shore communities in Britain

Abstract: Changes in rocky shore community composition as responses to climatic fluctuations and anthropogenic warming can be shown by changes in average species thermal affinities. In this study, we derived thermal affinities for European Atlantic rocky intertidal species by matching their known distributions to patterns in average annual sea surface temperature. Average thermal affinities (the Community Temperature Index, CTI) tracked patterns in sea surface temperature from Portugal to Norway, but CTI for communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 75 publications
(101 reference statements)
1
31
0
1
Order By: Relevance
“…The marine climate of the British Isles and Ireland has undergone oscillations throughout the 20th century, with the onset of global climate change first becoming evident in the late 1980s (Hawkins et al, 2003;Philippart et al, 2011). The warming trend has slowed down over the last decade (NOAA OISST; Reynolds et al, 2007) due to the climate-driven slowdown in the Atlantic Meridional Overturning Circulation (AMOC) causing a colder patch of surface water to the northwest of the United Kingdom 1 This has been reflected in changes in intertidal communities (Burrows et al, 2020). Despite the recent slowing of the warming trend in the United Kingdom, the impacts of climate change are still being experienced, especially the punctuation of pervasive climate change by extreme events (Firth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine climate of the British Isles and Ireland has undergone oscillations throughout the 20th century, with the onset of global climate change first becoming evident in the late 1980s (Hawkins et al, 2003;Philippart et al, 2011). The warming trend has slowed down over the last decade (NOAA OISST; Reynolds et al, 2007) due to the climate-driven slowdown in the Atlantic Meridional Overturning Circulation (AMOC) causing a colder patch of surface water to the northwest of the United Kingdom 1 This has been reflected in changes in intertidal communities (Burrows et al, 2020). Despite the recent slowing of the warming trend in the United Kingdom, the impacts of climate change are still being experienced, especially the punctuation of pervasive climate change by extreme events (Firth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of long-term trends in temperature on changes in the distribution and abundance of marine species are becoming better understood, with range limits shifting polewards (Poloczanska et al, 2013) and a shifting balance of species with colder thermal tolerance ranges (cold-affinity species) and species with warmer thermal tolerance ranges (warm affinity species) within communities (Burrows et al, 2019(Burrows et al, , 2020. Impacts of short-term variation in temperature, particularly marine heatwaves (Hobday et al, 2016), however, are less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Herbivorous gastropods (periwinkles and limpets) strongly affect the distribution of macroalgae, especially ephemeral species 16,17,31 . Unlike what has been predicted for the shores of Great Britain and western Europe, it is unlikely that southern species will expand their ranges northward to fill the gaps 10,32 . Recolonization of rocky intertidal shores in the Gulf of Maine after the last glacial retreat was by European species rather than range expansions of southern species 33,34 .…”
Section: Discussionmentioning
confidence: 72%
“…redictions about how climate change will affect marine ecosystems have been largely based on extrapolations from short-term experiments of physiological changes or retrospective surveys [1][2][3][4][5] . While the effects of climate change on the oceans are predicted to lead to declines in consumer biomass at mid and higher trophic levels and simplification of food webs [6][7][8] , there are few long-term, longitudinal surveys of populations in the wild to support these predictions 9,10 . Here, we provide evidence for decadal declines of five common benthic species (the tortoiseshell limpet, Testudinalia testudinalis, the common periwinkle, Littorina littorea, the dogwhelk, Nucella lapillus, the blue mussel, Mytilus edulis, and the barnacle, Semibalanus balanoides) on rocky shores of the NW Atlantic Ocean, and link these declines to changes in oceanic conditions in the Gulf of Maine due to climate change.…”
mentioning
confidence: 99%
“…The rocky intertidal zone is a useful arena to examine the ecological consequences of climate warming (Helmuth et al 2006). Long‐term monitoring efforts and resurveys of historical studies have demonstrated changes in the abundance (Southward 1991, Southward et al 1995), composition (Sagarin et al 1999, Burrows et al 2020), and phenology (Moore et al 2011, Poloczanska et al 2013) of intertidal plants and animals associated with recent warming trends. Moreover, the long history of manipulative experiments facilitates the discussion of ecological processes relevant to observational studies.…”
Section: Introductionmentioning
confidence: 99%